Análisis de contenidos presentados en la Fanpage de la Carrera de Comunicación de la Universidad Nacional de Chimborazo en el periodo enero 2023 - mayo 2024 - Robalino Latorre, Mercedes Itzayana (2025)
The objective of this research was to analyze the management of social media, particularly the Fanpage of the Communication Program at the National University of Chimborazo. The aim was to understand its relationship with institutional outreach, the construction of academic identity, and the strengthening of student community bonds. To achieve this, aspects such as the coherence of institutional discourse, content planning, the active participation of faculty and students, and the use of digital communication strategies were considered. The analysis of the results revealed discursive coherence between the university authorities and the way the Fanpage is managed. It also showed how academic activities are prioritized, how a sense of belonging is created through the use of audiovisual channels and resources, and how areas for improvement were identified, particularly regarding content segmentation. The research adopted a mixed-methods approach, combining qualitative techniques such as semi-structured interviews with authorities and staff of the Communication Program, and content analysis of the Fanpage posts during the 2023–2024 period. This provided a comprehensive view of the role social media plays and its impact at the institutional level.